Estimation of genetic parameters for the alkalinity tolerance trait in Urechis unicinctus - Wei Zhang; Juan Sui; Kai Wang; Mingyu Shao; Yongzheng Zhao; Hongtao Wang; Zongtao Chen; Zhifeng Zhang; Yubin Ma (Aquaculture Reports, 2025)
The echiura worm Urechis unicinctus has high nutritional and medicinal values and has been identified as a Chinese featured aquatic germplasm resource. However, overfishing and social demand have made it difficult to fill this market gap. The vast area of saline-alkali water in China remains a huge unexploited resource owing to its harsh environmental conditions. To address the scarcity of alkali-tolerant germplasm resources of U. unicinctus in China, we established 15 full-sib families derived from wild Qinhuangdao populations for systematic alkali stress experiments. The 72-h LC50 of U. unicinctus was determined to be 85.59 mM. We estimated the genetic parameters of the alkalinity tolerance trait in U. unicinctus for the first time and calculated the heritability of the alkalinity tolerance trait as 0.14 ± 0.06 (P < 0.05), which belongs to a low level of heritability, indicating that it can be improved by population hybridization, molecular breeding, and family selection breeding. In addition, the genetic and phenotypic correlation coefficients between the alkalinity tolerance trait and body weight were 0.97 ± 0.02 and 0.82 ± 0.02 (P < 0.01), respectively, with a Pearson correlation coefficient of 0.49 (P < 0.01). These results indicate that alkali tolerance is significantly correlated with body weight and that alkali tolerance can be selected indirectly through body weight. The results of this study provide valuable insights for the selection breeding of superior varieties with alkali tolerance in U. unicinctus and have important value in promoting the utilization of saline-alkali water resources.